Therapy options for adrenal insufficiency and recommendations for the management of adrenal crisis - Nowotny, Hanna (Endocrine, 2021)
Adrenal insufficiency (AI) is a life-threatening condition requiring life-long glucocorticoid (GC) substitution therapy, as well as stress adaptation to prevent adrenal crises. The number of individuals with primary and secondary adrenal insufficiency in Europe is estimated to be 20–50/100.000. A growing number of AI cases are due to side effects of GC treatment used in different treatment strategies for cancer and to immunotherapy in cancer treatment. The benefit of hormone replacement therapy is evident but long-term adverse effects may arise due to the non-physiological GC doses and treatment regimens used. Given multiple GC replacement formulations available comprising short-acting, intermediate, long-acting and novel modified-release hydrocortisone as well as subcutaneous formulations, this review offers a concise summary on the latest therapeutic improvements for treatment of AI and prevention of adrenal crises. As availability of various glucocorticoid formulations and access to expert centers across Europe varies widely, European Reference Networks on rare endocrine conditions aim at harmonizing treatment and ensure access to specialized patient care for individual case-by-case treatment decisions. To improve the availability across Europe to cost effective oral and parenteral formulations of hydrocortisone will save lives.